Studi Tentang Kompetensi Manajerial Kepala Sekolah Sebagai Upaya Peningkatan Profesionalitas Guru Di SD Negeri Timuhegar Kecamatan Bojonggambir Kabupaten Tasikmalaya - Asep Haryana (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
The background of this research is that the performance in carrying out managerial functions, a school principal will experience several obstacles caused by various factors both from outside and from within. A school principal is able to carry out the managerial function of the principal, if in carrying out this function it is carried out properly, and can overcome various obstacles that arise properly and wisely. With qualified managerial competency skills, it is hoped that teacher professionalism will also increase teacher professionalism. The purpose of this study was to analyze and describe: 1) Implementation of the principal's managerial competencies in improving teacher professionalism; 2) The obstacles faced by school principals in implementing the principal's managerial competencies to improve teacher professionalism; 3) Efforts made by the principal in implementing the managerial competency of the principal to improve teacher professionalism. The research method used in the preparation of this thesis is descriptive with a qualitative approach. Data collection techniques were carried out through interviews, observation, and documentation studies. The informants in this study included school principals, supervisors, school committees, and teachers. The results of the study show that 1) The managerial competence of the principal in review has been well implemented so that it can improve teacher professionalism. However, there are aspects that need to be improved, namely managing school change and development towards an effective learning organization; 2) There are obstacles encountered in applying the managerial competence of school principals in improving teacher professionalism; 3) There are efforts to overcome obstacles in implementing the principal's managerial competencies to improve teacher professionalism. The first obstacle is the difference in tasks that are very different because.